Multi-Level Governance of Hydropower in China? The Problem of Transplanting a Western Concept into the Chinese Governance Context - Hensengerth, Oliver (Multi-Level Governance: The Missing Linkages, 2015)
Abstract Purpose The chapter attempts to evaluate the utility of applying multi-level governance outside of the EU, and also outside of the group of democratic states, to states that have defied the third wave of democratization and that are characterized by a so-called new authoritarianism. The case is the People’s Republic of China, and the focus falls on policy-making and implementation in the field of hydropower with special attention to the issue area of environmental protection. Methodology/approach The chapter draws on the notion of scales and indigenous Chinese governance concepts and brings these into a conversation with the concept of multi-level governance. Case studies on hydropower decision-making in China contribute empirical data in order to investigate the utility of multi-level governance in the Chinese governance context. Findings The chapter argues that if multi-level governance is to have utility in other cultural contexts it needs to move away from a consideration of pre-given scales as locus of authority and consider indigenous governance concepts and notions of scale, and it crucially needs to map power relationships in the making and implementation of policies in order to reach analytical depth. Research implications The case of China shows that authoritarian regimes can be analysed in terms of multiple levels as authoritarianism no longer automatically implies strict top-down entities. Instead, autocracies can be highly fragmented and subject to complex decision-making processes that can arise during processes of administrative reform. This can lead to vibrant and reflexive systems of governance that exhibit adaptive skills necessary to ensure regime survival amidst a continuously diversifying society and changing external circumstances. As a consequence, a research programme looking at the new authoritarianism from a multi-level governance perspective has the capacity to uncover and describe new forms of governance, by bringing the concept into a conversation with indigenous governance concepts. Practical implications In China, informal networks between the energy bureaucracy and hydropower developers determine the hydropower decision-making process. This is particularly detrimental at a time when the Chinese government emphasizes the importance of the rule of law and social stability. Informal networks in which key government agencies are involved actively thwart the attempt of creating reliable institutions and more transparent and accountable processes of decision-making within the authoritarian governance framework. Social implications The findings show the dominance of informal networks versus the formal decision-making process. This sidelines the environmental bureaucracy and fails to fully realize the importance of public input into the decision-making process as one potential element of institutionalized conflict resolution. Originality/value The chapter builds on existing multi-level governance approaches and fuses them with notions of scales and indigenous Chinese governance concepts in order to enable the applicability of the concept of multi-level governance outside of its area of origin. This advances the explanatory depth and theoretical reach of multi-level governance.